Swot Analysis of Peatland Utilization Assessment for Community (Case Study at Banjar Regency of South Kalimantan) - Monica Rahardian Ary Helmina; Pusvita Indria Mei Susilowati; Alfian Misran (Journal of Wetlands Environmental Management, 2022)
Peatland is a unique, marginal, and fragile ecosystem. Its utilization must be based on thorough research and planning, and it needs supports from everyone. Yards, fields, and gardens are the forms that the community generally uses to utilize peatlands. This research aims to assess community's activities in the peatlands as their source of living and income. This research was conducted in Indonesia, specifically in the Province of South Kalimantan within an area with the biggest peatland contour. Descriptive data research was analyzed using thematic, socio-economic, and SWOT analysis. Research finding showed that farming is the suitable source of livelihood in the peatlands, besides plantation and other fields. The highest income from non-land activities on the peatlands are from entrepreneurship, physical service, and animal husbandry. People's general livelihood are as farmers whose prior commodity is with bigger average income than the province minimum wage per month. This is expected to describe that income from peatlands can make the ends meet of the community. This can also increase farmer's knowledge in cultivating their lands, the choice of plant type that is suitable with biophysical conditions of the peatlands. To work on the limit of the community's knowledge, activities and solutions from the experts on how to deal with farmer's problems in cultivating peatlands, are needed. Agroforestry technique is very suitable to analyze the source of livelihood. As forms to reserve lands in a farming world, the use of husk charcoal is also suggested. It has abundant benefits. It is often used for soil loosening, even for composting. Farmers make use of it for making compost, bokashi, Takakura, planting media, and seedbed media.